IMPLEMENTATION OF RESTORATIVE JUSTICE PRINCIPLES IN TERMINATING PROSECUTION OF MINOR CRIMES BY THE PROSECUTOR'S OFFICE OF THE REPUBLIC OF INDONESIA - Sumbodo, Dicky Dharmawan; Supanto (Journal of International Islamic Law, Human Right and Public Policy, 2025)
The law has the duty to ensure legal certainty in public life. But in reality, often law enforcement ends in legal injustice. The root of this unfairness stems from the ineffectiveness of the judicial system non society. Restorative justice is a term employed within the domain of criminal law. The indonesian prosecutor's office has released prosecutor's regulation number 15 of 2020, which deals with the discontinuation of legal proceedings through the use of restorative justice (PKRI 15/2020). Restorative justice is a method of resolving criminal cases that involves actively engaging the offenders, victims, their families, and other relevant individuals in order to achieve a fair conclusion. This strategy emphasises the reinstatement of the aggrieved parties to their initial condition, rather than pursuing revenge. The reasons for ending legal proceedings include restoring a fair state of affairs, safeguarding public interest, following the principle of proportionality, using punishment as a final option, and considering efficient, straightforward, and cost-effective proceedings